Uma história da Sociedade Brasileira de Matemática durante o período de 1969 a 1989: criação e desenvolvimento - Santos, Viviane de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Este trabalho situa-se dentro da linha de pesquisa História da Matemática no Brasil. Focaliza-se uma instituição de Matemática, a Sociedade Brasileira de Matemática (SBM), a fim de investigar um histórico da criação, das atividades e das publicações dessa Sociedade, bem como das pessoas envolvidas com a mesma em suas duas primeiras décadas de existência (1969-1989). O trabalho foi escrito com base nas atas das Reuniões do Conselho Diretor da SBM, seguido de outras fontes como entrevistas e publicações da Sociedade em questão.

This work is situated within the line of research History of Mathematics in Brazil. Focuses a Mathematics institution, the Brazilian Society of Mathematics (SBM) in order to investigate a historical of the creation, of the activities and of the publications of this society, as well as of the people involved with the same in his first two decades of existence (1969-1989). The work was written based on the minutes of the meetings of the Board of SBM, followed by other sources such as interviews and publications of the society in question.
A history of Brazilian Society of Mathematics during the period of 1969 to 1989: creation and development
Keywords: Sociedade Brasileira de Matemática; História da Matemática no Brasil; Sociedades Científicas; Brazilian Society of Mathematics; History of Mathematics in Brazil; Scientific Societies